Role of a bone conserving short stem femoral component in revision total hip arthroplasty: A case report - Thorat, Babaji (J Clin Orthop Trauma, 2020)
Choice of the implant during revision total hip arthroplasty (THA) is crucial in younger patients due to the impaired quality of bone and deficient bone stock. The short femoral stem provides an appealing unorthodox alternative implant in young patients undergoing primary total hip arthroplasty. A classic revision total hip arthroplasty predominantly describes the use of conventional or long stem for revision of the femoral component. However, little is known about the use of short femoral stem in revision THA. This case report discusses the revision of cemented conventional femoral stem using a bone-conserving short-stem femoral implant with circumferential metaphyseal fixation, which is seldom reported in the literature. Associated benefits are less aggressive surgery with a reduction in blood loss, magnitude and duration of surgery by avoiding the removal of distal cement in the femur canal, thus making the femoral component revision easier. Moreover, it facilitates postoperative rehabilitation and recovery as well. Also, it preserves the femoral bone stock and offers a long term solution especially in young patients retaining the choice of using a conventional or long stem femoral implant should a second revision becomes imperative.